JEJAK KOLONIAL CERPEN â€œBATAVIA YANG TAK SESUAI RENCANA LUCRETIAâ€ KARYA SASTI GOTAMA - Risen Dhawuh Abdullah (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
This study aims to describe the colonial trace contained in the short story "Batavia yang Tak Sesuai Rencana Lucretia" by Sasti Gotama which was published in Harian Kompas on January 15, 2023 from the perspective of hybridity, mimicry, and ambivalence. The approach used is a postcolonial study developed by Homi K. Bhabha. The qualitative-descriptive method was chosen in this study. The findings in this study are: first, the character Lucretia van der Maas absorbs Eastern cultural values due to living in indigenous areas for quite a long time, namely practicality in dress and this is opposed by Bastiaan van der Maas; secondly, the character Lucretia van der Maas experiences ambivalence in the form of refusing that she is equal to the character Catia while at the same time accepting that on the basis of religion, the moral mimicry as mockery is carried out by the character Catia; and third, the mimicry of language used by the coachman when addressing the figure of Lucretia van der Maas and the response to it which represents a more respectable European nation.